An experimental study on the mechanical properties of solid clay brick masonry with traditional mortars. (15th October 2022) - Soleymani, Abed; Najafgholipour, Mohammad Amir; Johari, Ali
Abstract: An experimental study is carried out to investigate the mechanical properties of clay brick masonry fabricated using traditional mortars. In this regard, four types of mortar whose frequent uses in Iranian traditional and historical monuments have been reported in the literature are selected. These mortars are gypsum mortar and three types of lime-based mortars including, Sarooj, lime-sand mortar, and lime-cement-sand mortar. In this study, tests on brick units, mortar specimens, masonry prisms and wallettes are conducted. The compressive stress-strain behavior, compressive strength, elastic modulus, and rupture modulus of mortars are determined from the standard tests. Moreover, the compression test of masonry prisms, direct shear test of brick-mortar bond, and diagonal shear test of masonry wallettes are carried out. The compressive stress-strain behavior of masonry and the shear bond strength of brick-mortar interface are determined from the tests on masonry prisms. Furthermore, shear stress-strain behavior of masonry wallettes is evaluated through diagonal shear tests. Some key mechanical properties of masonry wallettes such as modulus of rigidity and Poisson's ratio are also found from the test results. Accordingly, the brick-mortar bond governed the in-plane shear behavior of the masonry wallettes in diagonal shear tests. Furthermore, the highest compressive strength, elastic modulus, and diagonal shear strength belong to the masonry fabricated with gypsum mortar. By using the results of the experimental program, the applicability of some well-known empirical formulations for estimating the compressive strength of masonry prisms as well as the accuracy of idealized stress-strain models proposed for masonry material, are assessed. Highlights: An experimental study is carried out to investigate the mechanical properties of clay brick masonry with traditional mortars Masonry fabricated with gypsum mortar and three types of lime-based mortars are considered The compressive stress-strain behavior, compressive strength, elastic modulus, and rupture modulus of mortars are determined Compression test of masonry prisms, shear test of brick-mortar bond and diagonal shear test of masonry panels are carried out The applicability of well-known empirical formulations for estimating the compressive strength of masonry prisms is assessed